Gonadoblastoma: an immunohistochemical study and comparison to Sertoli cell nodule with intratubular germ cell neoplasia, with pathogenetic implications. Issue 6 (8th October 2014) - Kao, Chia‐Sui; Ulbright, Thomas M; Idrees, Muhammad T
<x xml:space="preserve">Abstract</x> Aims To investigate the immunohistochemical properties of the sex cord cells of gonadoblastoma and Sertoli cell nodule with intratubular germ cell neoplasia unclassified (IGCNU) as a means of objective distinction and to provide insight into the pathogenesis. Methods and results Immunohistochemical stains for SOX9, FoxL2 and SF‐1 were performed on 10 gonadoblastomas (all phenotypical females) and 14 Sertoli cell nodules with IGCNU in normal phenotypical males with coexisting germ cell tumours. The sex cord cells of gonadoblastomas showed strong, diffuse FoxL2 and SF‐1 positivity and focal weak to moderate SOX9 reactivity, whereas those of Sertoli cell nodules with IGCNU were uniformly, strongly positive for SOX9 and SF‐1, while negative for FoxL2. Conclusions Coexpression of SOX9 and FoxL2 in the sex cord cells of gonadoblastomas provides evidence that these morphologically ambiguous sex cord cells are incompletely differentiated. The strong, diffuse SOX9 and SF‐1 positivity and absence of FoxL2 reactivity in the Sertoli cell nodules with IGNCU support full Sertoli cell differentiation of the sex cord cells and distinguish them from gonadoblastomas. Deficient SOX9 expression in gonadoblastoma supports a current model of pathogenesis where immature germ cells, in the absence of well‐formed Sertoli cells, retain a fetal phenotype and susceptibility to malignant transformation.